The Effect of Psychology on Economic Change - Widarni, Eny Lestari; Febiyana, Rahma; Bawono, Suryaning (Asia Pacific Journal of Management and Education (APJME), 2022)
The aim of this study is to investigate existing research ideas about the factors that contribute to positive psychology and their influence on economic transformation. We use Content Analysis to compile scientific papers from Emerald, Science Direct, Sciendo, and Korean science, as well as books produced by psychology and economics professionals. Adaptation, empowerment of human resources, a sense of hope, optimism, and fortitude are considered psychological assets that can be taken by workers when facing problems or obstacles in the workplace. Psychology also affects the economy of workers. In carrying out economic development, in this century there is a method called Information Economy. Information Communication Technology is driving this change process. The information economy emphasizes the importance of technological capital in humans. Changes in the Information Economy are largely determined by political influences (interests of state regulators) and financial factors (availability of the required volume of financial resources). The information economy can strike a balance in four main directions: The balance of infrastructure and its readiness for use in society and its impact on business; state regulation and market self-management; existing and new information; and external exchange of information. In building a balanced information economy, there are several obstacles, one of which is a resource deficit.